Dence of Postoperatve Deep Vein Thrombosis:A Study of 150 Cases - Sarker, Mohammed Abu Kawsar; Amin, Md Abdullah Al; lslam, Md Johirul; Nuruzzaman, AKM; Bhattacharjee, Avisak (Journal of Surgical Sciences, 2019)
Background: Venous thromboembolism remains a common cause of morbidity and sometimescause of death in surgical practice. In developed world about 10% of hospital deathsare due to pulmonary embolism resulting from deep vein thrombosis( DVT). DVT in Asiancountries is not a rare condition. Objective: The purpose of the study was to find the incidence ,demgraophic characterand risk factors of deep vein thrombosis. Methods: 150patients undergoing emergency or elective operation of more than one hourof duration was selected for study. Patients evaluated by history, clinical examination andduplex scan. Collected analyzed by computer program. Results: 102 cases were male and 48 cases were female. The incidence of DVT in malewas 36.3% while among females it was 27.5%. venous thrombosis in age group above 50yrs is quite high, (43.33%) . One-fifth of the DVT patients were smokers. Longer duration ofoperation procedure was correlated with development of DVT and development of DVT waslittle higher in emergency operation than elective one. The occurrence of the condition insome co-morbid states especially diabetes mellitus (36. 7%) and cancer (33.3%) is noteworthy.Out of 51 DVT patients more than 84% developed sub-clinical DVT. Conclusion: In Bangladesh it is assumed that DVT is rare. But the current study revealsthat the incidence of postoperative DVT in Bangladesh is not that much rare event. Journal of Surgical Sciences (2016) Vol. 20 (2) :42-45